Biggest Public Oil Companies: Impact of External and Internal Factors on Capitalization - R. M. Nureev; E. G. Busygin (Финансы: теория и практика, 2019)
Estimate and search for factors that influence the capitalization of public oil companies are of great interest to researchers. The impact of various external and internal factors on the value of oil companies’ stocks was considered. This includes changes in oil prices, stock market index movements, inflation fluctuations, financial and production indicators. The study includes building models with calculated standard errors by the Driscoll-Kraay method based on quarterly data for the eight biggest public oil companies operating in the upstream and downstream segments, from the first quarter of 2006 to the third quarter of 2017. Such indicators as total oil production by OPEC countries, greenhouse gas emissions by companies, and the sum of shareholder’s funds owned by large institutional investors were used for the first time when building the model to identify factors affecting the market capitalization of oil companies. One of the key results is the conclusion that quarterly production volumes turned out to be the most significant factor having a positive impact on the cost of oil firms. That is, investors are laying the idea of compensating for losses from lowering the cost of oil by increasing its production and selling a larger volume in the value of shares in companies. At the same time, such indicators of production efficiency as profitability in the upstream and downstream segments lose their significance depending on the period under consideration.